An experimental investigation of the finite amplitude wave - KOZACZKA, W.; GRELOWSKA, G. (Archives of Acoustics, 1999)
An experimental investigation of the pressure field distribution produced by a plane circular piston in water was carried out by means of two receivers of different size. A transducer of 46-mm-diam and 1.0-MHz center frequency was used as a transmitter. The PVdF needle hydrophone of 1mm diameter was the first receiver, whereas the second one had a diameter equal to that of the source. All experiments were performed using a high precision computer-controlled tank facility. Measurements of harmonic generation are compared with numerical calculations based on the nonlinear parabolic wave equation.